Social Preneurship Training For Rappokaling Pkk Women Of Makassar City - Daga, Rosnaini; Negara Salam, Karta; Hamdat, Aminuddin; Pratiwi Ar, Dhita (Patria Artha Journal of Community (PKM), 2021)
This activity is purposed to support the welfare of urban communities through empowerment and gender approaches, namely the empowerment of women through Family Welfare Program by fostering social development in PKK organizations and activities. Method : This activity was carried out by providing skills training according to partner interests then partners will be able to produce superior products that have the economic value needed by the market. In order to produce a product with high economic value. The efforts to foster social development, entrepreneurship that has social goals (welfare of the community) and is based on social activities, partners will also be given training on entrepreneurial motivation and entrepreneurial managerial skills, which includes production management, financial management, simple accounting and marketing management. The assistance is provided to partners, so that efforts to foster social preneur activities in Family Welfare activities can be realized and run well.